Artificial Intelligence in Lebanese Upper Elementary Science Classrooms: Readiness, Practices, and Pedagogical Impact - Habib Badawi; Adiyono Adiyono (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
The integration of artificial intelligence (AI) into K–12 education raises urgent questions about pedagogical quality, teacher readiness, and educational equity. The present investigation examines AI readiness, classroom practices, and pedagogical impact in Lebanese upper elementary science education, a context shaped by structural inequality, fragile infrastructure, and growing educator interest in digital transformation. A convergent parallel mixed-methods design was employed, combining structured teacher surveys adapted from DigCompEdu and Technological Pedagogical Content Knowledge (TPACK)-validated instruments, systematic classroom observations, and semi-structured interviews with teachers and school leaders across public and private Lebanese schools. Findings reveal that participating teachers predominantly occupy intermediate DigCompEdu competence levels (Integrator to Expert), demonstrating functional digital competence but significant underdevelopment in higher-order AI pedagogical integration. Classroom practice predominantly relies on substitutive, Replacement-level AI use, while only a small number of better-resourced private schools implement transformative, AI-enabled science instruction. Barriers to integration are structural and systemic rather than motivational, with significant sector differences confirmed across all key competence and readiness measures. Significant equity disparities in AI access, professional development, and pedagogical impact persist across public and private school sectors. The investigation also identifies five underacknowledged pedagogical risks: teacher deskilling, the erosion of epistemic authority, generative AI hallucination hazards, algorithmic opacity in assessment, and the hidden curriculum of AI-mediated knowledge, and it argues that policymakers and practitioners must address these risks alongside structural challenges. The study further provides evidence-based policy recommendations for the Lebanese Ministry of Education, school leaders, and the research community, and outlines implications for the wider MENA region.